Assistance for NIB Registration in an Effort to Increase Legality and Competitiveness of MSMEs in Simoangin-angin Village - Syarif, Muhammad Zulfan; Nisa, Fauzatul Laily; Oktafia, Renny (Pascasarjana Universitas Mataram, 2025)
Micro, Small, and Medium Enterprises (MSMEs) play a vital role in regional economic development, yet many MSME owners lack a Business Identification Number (NIB). This community service aimed to enhance business legality and competitiveness through NIB registration assistance in Simoangin-angin Village, Wonoayu, as part of the BPS Statistics Office's Desa Cantik (Statistics-Loving Village) program. The methods used were socialization and assistance, both in-person and online. The program involved 80 micro-business owners, resulting in 12 NIBs created during direct assistance and 28 NIBs through online assistance. Main obstacles included technological limitations and lack of response in online processes. The program successfully increased MSME owners' understanding of NIB importance and statistical literacy, while providing broader access to business development opportunities